Neurotensin receptors in pancreatic ductal carcinomas - Körner, Meike (EJNMMI Res, 2015)
BACKGROUND: The frequent expression of neurotensin receptors (NT-R) in primaries of pancreatic ductal carcinomas has triggered the development of radioactive neurotensin analogs for possible in vivo targeting of these tumors. However, the complete lack of information regarding NT-R in liver metastases of pancreatic cancer and pancreatic intraepithelial neoplasia (PanIN) makes an in vitro study of NT-R in these tissues indispensable. METHODS: Using in vitro receptor autoradiography with (125)I-[Tyr(3)]-neurotensin, NT-R were investigated in 18 primaries and 23 liver metastases of pancreatic ductal carcinomas as well as in 19 PanIN lesions. RESULTS: We report here that 13 of 18 ductal carcinoma primaries and 14 of 23 liver metastases expressed NT-R. Moreover, none of the six PanIN 1B cases expressed NT-R, while two of six PanIN 2 and five of seven PanIN 3 expressed NT-R. Binding was fully displaced by the type 1 NT-R-selective antagonist SR48692, indicating that the NT-R in the tumors are of the type 1 NT-R subtype. CONCLUSIONS: These in vitro data extend the currently available information on NT-R in invasive and non-invasive pancreatic ductal tumors. They suggest that type 1 NT-R may be a novel, specific marker of PanIN of higher degree. The high expression of NT-R in primaries and metastases of invasive cancer strongly support the need to develop radioactive neurotensin analogs for the diagnosis and therapy of this tumor type.